HR Metaverse Leadership: Mengelola Identitas dan Budaya Kerja di Ruang Kantor Virtual 3D : (Fokus: Bagaimana pemimpin SDM membangun loyalitas saat interaksi dilakukan melalui avatar) - Moh Choirus Samroni; Arikatul Jannah; Najnatul Mismah; Mochammad Isa Anshori (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
Digital transformation has driven organizations to adopt the metaverse as a 3D virtual workspace that enables employee interaction through avatars, thereby introducing new challenges in managing organizational identity, work culture, and employee loyalty. This study aims to analyze the role of human resource leadership in establishing organizational identity, transforming work culture, and sustaining employee loyalty within a metaverse-based work environment. The study employs an integrative literature review approach by systematically collecting and synthesizing relevant scholarly sources from reputable publications within the last five years. The findings indicate that organizational identity in the metaverse is constructed through avatar representation and virtual environment design, while work culture undergoes a transformation toward flexible digital interaction patterns that still require reinforcement of organizational values. Furthermore, employee loyalty is influenced by the quality of virtual experiences and the effectiveness of leadership communication. In this context, digital-based HR leadership emerges as a critical factor in fostering employee engagement and trust in a non-physical interaction setting. This study contributes conceptually by integrating leadership, identity, culture, and loyalty within the metaverse framework, and provides practical implications for organizations in designing adaptive human resource management strategies in response to the advancement of immersive technologies.